Biped Robot: Balance Center of Gravity on Uneven or Smooth Terrain - R. , Hariharan; Ahamed Palayam, Muzammil; A. , Naved Ahmed; M. , Musthafa Kamil; K. , Mohamed Yasin (International Journal of Psychosocial Rehabilitation, 2024)
We present a system whereby the human motion is replicated so as to provide cost-effective methods to move the biped robots into the industrial age, which is still tender with articulated and collaborative robots by using a maximum of 7-axis freedom of motion and rover robots with less agility over lands of war to mimic human movements in battle zones. This led us to devise a biped robot for better walking and balancing. Its mechanical structure, including the joint configuration and specification, the structure of the knee joint, the speed reduction mechanism in the servo motor by programming, and the mechanical cross bracing used, are described in detail. A specific control system (ATmega2560) on the Mega 2560 (Arduino Board) for bipeds that is a serial and distributed network and consists of a microcontroller, bootloader, servo input and output pins, sensor input and output pins, and TWI/I2C system. With the developed biped robot, biped walking and one-leg balancing and weight shifting while walking for better gate motion in 5000 [ms] are implemented as basic and verification experiments for fast walking and balancing.